Characterisation of the methylation pattern in the intragenic CpG island of the IGF2 gene in Bos taurus indicus cumulus cells during in vitro maturation - Franco, Mauricio Machaim; Fagundes, Nadia Simarro; Michalczechen-Lacerda, Valquiria Alice; Caixeta, Ester Siqueira; Rodrigues, Fernanda de Castro; Machado, Grazieli Marinheiro; Ferreira, Allice Rodrigues [UNESP]; Nunes Dode, Margot Alves (Springer, 2014)
The aim of this study was to characterise the methylation pattern in a CpG island of the IGF2 gene in cumulus cells from 1-3 mm and a parts per thousand yenaEuro parts per thousand 8.0 mm follicles and to evaluate the effects of in vitro maturation on this pattern.Genomic DNA was treatment with sodium bisulphite. Nested PCR using bisulphite-treated DNA was performed, and DNA methylation patterns have been characterised.There were no differences in the methylation pattern among groups (P > 0.05). Cells of pre-IVM and post-IVM from small follicles showed methylation levels of 78.17 +/- 14.11 % and 82.93 +/- 5.86 %, respectively, and those from large follicles showed methylation levels of 81.81 +/- 10.40 % and 79.64 +/- 13.04 %, respectively. Evaluating only the effect of in vitro maturation, cells of pre-IVM and post-IVM COCs showed methylation levels of 80.17 +/- 12.01 % and 81.19 +/- 10.15 %.In conclusion, the methylation levels of the cumulus cells of all groups were higher than that expected from the imprinted pattern of somatic cells. As the cumulus cells from the pre-IVM follicles were not subjected to any in vitro manipulation, the hypermethylated pattern that was observed may be the actual physiological methylation pattern for this particular locus in these cells. Due the importance of DNA methylation in oogenesis, and to be a non-invasive method for determining oocyte quality, the identification of new epigenetic markers in cumulus cells has great potential to be used to support reproductive biotechniques in humans and other mammals.
Keywords: Bovine; Cumulus cells; IGF2; Epigenetics; DNA methylation; In vitro maturation